CT Scanning Findings in Clinically Diagnosed Cerebral Palsy - Wahed, Md Abdul; Hossain, Md Altaf (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Cerebral Palsy is a non-progressive disorder due to insult in the developing brain. This causes disorders in muscle tone, posture and movement. Cerebral palsy is usually diagnosed by clinical features. Though risk factors are identified in about 75% of cases, the etiology remains unclear. Magnetic resonance imaging is the standard method to detect central nervous system abnormalities; but in resource poor areas CT Scanning may be an alternative method to elucidate the underlying Central Nervous System abnormalities. Objectives: The objective was to detect CT Scanning findings in different types of Cerebral palsies. Methodology: This was a prospective and cross-sectional study conducted on 525 Children registered at Child Development Center attached to Rangpur Mother and Children Hospital. Cerebral palsy was diagnosed by using an Interview Schedule. During from 1.1.2016 to 31.12.2019 CT scanning of brain was performed purposefully to all children to detect the underlying Central Nervous System abnormalities. The purpose was explained to parents and consent was taken before performing the tests. The children were in sedation during the procedure. Result: A total of 1800 registered children, 525 (29.10%) children were suffering from Cerebral Palsy. The male and female ratio was 3:2 and age distribution was 2.6±1.5 years. Seventy nine percent (79.0%) of children came from poor families. Parental education up to class V was in 65% cases. Maximum number (63.0%) of cases was suffering from spastic type of Cerebral Palsy followed by athetoid type (18.3%) and 7.1% ataxic type. Among spastics, quadriplegia was present in 68.5% of cases followed by hemiplegia (18.5%). Perinatal asphyxia was the commonest (56.1%) risk factor of Cerebral Palsy. Among all the CTs 116 (22.0%) were with normal finding and 409 (78.0%) were with various types of abnormal findings. White Matter Injury was present in 79 (15.0%) of cases and among these volume loss in periventricular areas with ventricular dilatation and deep white matter damage was common. The next abnormalities were Focal Vascular Insults (9.0%), Malformations (5.0%) and Unclassified lesions (4.0%). Grey Matter Injury was common in spastic type of cerebral palsy but there was much overlapping of abnormal findings and most (66.3%) insults occurred in perinatal period. Conclusion: CT scanning of brain is a comparable test to detect the central nervous system abnormalities in resource poor areas. Grey matter injury is the common abnormality in Cerebral palsy but there is much overlapping between CT Scanning findings and clinical diagnosis. J Bangladesh Coll Phys Surg 2022; 40: 31-38